Factors associated with malnutrition among children in internally displaced person's camps, northern Uganda - Olwedo, Mary Abwola (Makerere Medical School, 2008)
INTRODUCTION: Since mid 1990s, Uganda has had an estimated 1.6 million internally displaced persons (IDPs) in the northern and eastern districts. A major cause of morbidity and mortality amongst children in displaced settings is protein energy malnutrition. OBJECTIVE: To estimate the prevalence of and describe the risk factors for protein energy malnutrition among under five years old children living in internally displaced persons camps in Omoro county Gulu district. METHODS: This was a cross sectional study undertaken among internally displaced people's in Omoro county, Gulu district during 13 – 23(rd) September 2006. Anthropometric measurements of 672 children aged 3 – 59 months were undertaken and all their caretakers interviewed. The anthropometric measurements were analyzed using z-scores of height-for-age (H/A) and weight-for-height (W/H) indices. Qualitative data were collected through 6 focus group discussions, key informant interviews and observation. Data were captured using Epi Data version 3.0 and analyzed using EPI-INFO version 3.3.2 and SPSS version 12.0 computer packages respectively. ResultsThe prevalence of global stunting was found to be 52.4% and of global acute malnutrition 6.0%. Male children are at risk of being stunted Adjusted OR 1.57 95% CI 1.15–2.13; p value=0.004. Children in the age group 3 – 24 months were at risk of acute malnutrition Adjusted OR 2.78 95% CI 1.26–6.15; p value=0.012 while de-worming was protective Adjusted OR 0.44 95% CI 0.22–0.88; p value=0.018. The main sources of foodstuff for IDPs include food rations distributed by WFP, cultivation and purchase. CONCLUSION AND RECOMMENDATIONS: There is high prevalence of protein energy malnutrition (stunting) among children in the internally displaced people's camps in Gulu district. Male children are at an increased risk of stunting while children aged between 3 – 24 months are at an increased risk of suffering from acute malnutrition. Stakeholders including local government and relief organizations should intensify efforts to improve the nutritional status of IDPs especially children in the camp settings. The quantity of and access to household food supplies, health education on infant and child feeding and integrated management of childhood illnesses (IMCI) activities in the camps should be strengthened.